EVOLUTION PROCESS FOR MIGRATION OF TRADITIONAL NETWORKS IN TO NGIN - Forte Moreno, Aileen; Anías Calderón, Caridad; Cecilio Núñez, Yoan Larry (Telemática, 2020)
Traditional Intelligent Networks (IN) systems have entered a stage of technological obsolescence in the market; however, value-added services maintain an important role to continue being offered, mainly to users and companies. In this way, operators must look for solutions to maintain the service and in some cases make use of existing networks. The evolution of IN to the New Generation Intelligent Grids (NGIN) is an imminent need, but sometimes it is unknown how the evolution process is. This article allows operators to migrate to new innovative IN solutions from their existing networks. They can abstract and solve problems of interaction of characteristics resulting from the composition of services from heterogeneous network domains. To guarantee the complete migration of the functionalities to new platforms, the Historical-logical, Scientific and Deductive methods were used, which allow visualizing the evolution, scientific verification and analysis of standardized requirements and demands, fundamental in the evolution from IN to Multimedia Subsystem Internet Protocol (IMS). These solutions make it possible to provide new IN services in IMS and enrich existing IN services with Internet and web domain services.